2007
DOI: 10.1007/s11156-007-0068-1
|View full text |Cite
|
Sign up to set email alerts
|

Are candlestick technical trading strategies profitable in the Japanese equity market?

Abstract: Candlestick, Technical analysis, Japan, Market timing, G12, G14,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 21 publications
0
23
0
15
Order By: Relevance
“…Another study by Marshall et al (2008) investigated the profitability of the old famous market timing technique; candlestick in Japanese equity market during the 1975-2004 time horizon using daily price data for the largest 100 stocks that were included on Tokyo Stock Exchange.…”
Section: Published By Sciedu Press 30 Issn 1927-5986 E-issn 1927-5994mentioning
confidence: 99%
“…Another study by Marshall et al (2008) investigated the profitability of the old famous market timing technique; candlestick in Japanese equity market during the 1975-2004 time horizon using daily price data for the largest 100 stocks that were included on Tokyo Stock Exchange.…”
Section: Published By Sciedu Press 30 Issn 1927-5986 E-issn 1927-5994mentioning
confidence: 99%
“…The profitability of candlestick trading strategies is further confirmed by Goo et al (2007), Lu et al (2012) and Lu (2014). On the other hand, Marshall et al (2006Marshall et al ( , 2008 and Horton (2009) find that candlestick trading strategies do not have any predictive value for major equity markets. In addition, Fock et al (2005) and Duvinage et al (2013) employ 5-min data to investigate the German bond futures market and the U.S. stock market, respectively, and both conclude that candlestick trading strategies do not improve investment performance.…”
Section: Introductionmentioning
confidence: 77%
“…The second type of trend is the EMA 10 trend proposed by Marshall et al (2006), and is also used in Marshall et al (2008). The EMA 10 trend is defined as a ten-day exponential moving average of closing prices, as follows:…”
Section: Trend Definitionsmentioning
confidence: 99%
“…Underpinning these findings is a study by Marshall (2008) who found that the technical analysis was not profitable tool once it is applied on large stocks in the Japanese market over the 1975-2004. Marshall (2008 was examining candlestick test in the Japanese equity market.…”
Section: Literature Reviewmentioning
confidence: 99%